The at-Risk Student: Answers for Educators - Ogden, Evelyn Hunt; Germinario, Vito (Rowman & Littlefield Publishers, 1994)
An excellent resource that should be on the desk of every student assistant professional as well as every administrator. It gives step-by-step procedures in identifying high risk students who are a challenge for our schools.